Self-regulated learning: does it affect mathematics learning outcomes? - Handican, Rhomiy; Riva Darwata, Siti; Ananda, Azwar; Mukhaiyar, Mukhaiyar (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2022)
Many factors can affect student learning success, especially math learning outcomes which are considered a difficult subject by students. One of the factors is the self-regulation system in learning. Self-regulation system or known as self-regulated learning is certainly different among students. So, the purpose of this study is to determine the level of self-regulated learning and its effect on math learning outcomes. This research is quantitative research using an on-experimental research type with a survey method. The sample used in this study amounted to 40 students who were taken randomly using simple random sampling. While data collection was done with questionnaires and documentation. The data were analyzed using the Pearson product-moment test. From the results of the analysis at a significant level of 5%, it was concluded that there was a significant influence between self-regulated learning on students' math learning outcomes. With the contribution of variable X to variable Y amounting to 32.49%. This means that 32.49% of students' math learning outcomes are determined by self-regulated learning and 67.51% are determined by other variables that are not studied